2022
DOI: 10.14309/ajg.0000000000002054
|View full text |Cite
|
Sign up to set email alerts
|

Patient Knowledge, Risk Perception, and Barriers to Barrett's Esophagus Screening

Abstract: INTRODUCTION: Most patients with esophageal adenocarcinoma (EAC) do not have a previous diagnosis of Barrett's esophagus (BE), demonstrating a failure of current screening practices. An understanding of patient attitudes and barriers is essential to develop and implement interventions to improve BE screening adherence. METHODS:We conducted a Web-based survey of patients aged >50 years with chronic gastroesophageal reflux disease at 3 academic medical centers and 1 affiliated safety net health systems. Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…About one fifth (20.4%) of patients admitted fear of discomfort as a barrier to undergoing screening UE, along with logistical considerations (e.g., scheduling, location, wait time, post-sedation/post-anesthesia needs etc.,); this concern was increased among patients who had never undergone a prior UE. [18] Interestingly, more Black respondents recognized the importance of screening and were more concerned about developing BE/EAC compared to White and other race groups, but more frequently reported difficulty with scheduling the procedure. This suggests that non-endoscopic approaches such as EsoCheck and EsoGuard (EC/EG) could reduce inequity and be instrumental in improving acceptability and accessibility of BE testing among individuals who might otherwise be unable or unwilling to comply with traditional diagnostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…About one fifth (20.4%) of patients admitted fear of discomfort as a barrier to undergoing screening UE, along with logistical considerations (e.g., scheduling, location, wait time, post-sedation/post-anesthesia needs etc.,); this concern was increased among patients who had never undergone a prior UE. [18] Interestingly, more Black respondents recognized the importance of screening and were more concerned about developing BE/EAC compared to White and other race groups, but more frequently reported difficulty with scheduling the procedure. This suggests that non-endoscopic approaches such as EsoCheck and EsoGuard (EC/EG) could reduce inequity and be instrumental in improving acceptability and accessibility of BE testing among individuals who might otherwise be unable or unwilling to comply with traditional diagnostic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The over-representation of individuals with GORD symptoms, higher education, upper endoscopy experience, or who knew someone with oesophageal cancer suggests that self-selection bias is likely to have occurred. These groups are all associated with having more favourable perceptions of BO/OAC screening,13 15–17 25 potentially limiting the generalisability of our findings to the general population. Furthermore, patients with BO were prone to a familiarity preference effect,31 with individuals tending to prefer tests (conventional endoscopy in this case) merely because they are familiar with it.…”
Section: Discussionmentioning
confidence: 85%
“…To guide the design of an effective screening strategy, it is important to gain a more comprehensive understanding of individuals’ general willingness to be screened for BO/OAC irrespective of the test used. Previous surveys and screening trials suggested that the presence of GORD symptoms and easily accessible test options may play an important role in screening motivation 13 15–17. However, the potential influence of socioeconomic factors, social stigma, and involvement of the general practitioner on willingness to be screened for BO/OAC remain largely untouched 18…”
Section: Introductionmentioning
confidence: 99%
“…[23, 24] This is likely multifactorial in nature, including the absence of specific symptoms associated with BE, poor patient understanding of their own disease risk, and fears around the discomfort or inconvenience of upper endoscopy. [25] Office-based, non-endoscopic testing with EC/EG can address these patient concerns by improving accessibility and minimizing invasiveness. Additionally, given the intended utility of EsoGuard as a high-sensitivity triage test, it is expected that the test positivity rate should be higher than true disease prevalence, so as not to risk missing any patients with disease.…”
Section: Discussionmentioning
confidence: 99%